Implementation Of Restorative Justice By The Police On Defaming In Social Media - Gloryna Rahayu Chrysti (Universitas Negeri Gorontalo, 2021)
Abstract : The purpose of this research is to unravel the implementation of restorative justice by the police in criminal acts of defamation on social media, especially those that occur in the jurisdiction of the Gorontalo Regional Police. This type of research is empirical legal research using a field approach through interviews, supported by a statute approach and a case approach . The analysis used in this study is descriptive data analysis using a qualitative approach to secondary data and primary data. Based on the results of the study, the answers to the existing problems were obtained, that the effectiveness of the implementation of restorative justice by the police in the criminal act of defamation on social media in the Gorontalo Regional Police jurisdiction has actually been running in accordance with the expected restorative justice, although in its implementation it is still far in quantity when compared to the number of cases entered and processed through RJ. In 2019, 2020 and 2021 there were 11 cases of defamation that were resolved through RJ at the Gorontalo Regional Police and it is a success of the police as a mediator for resolving cases before entering the legal court process, the police have played their role in providing mediation offers to the parties in pursue restorative justice. All components involved in restorative justice or a restorative justice approach must implement in an integrated manner between the police, litigants, and community leaders as well as traditional leaders in cases of criminal defamation on social media.